Factors of job satisfaction of non-medical employees in healthcare industry - MONICA, DR. BENITA. S.; MS. S. RENUGADEVI (The journal of contemporary issues in business and government, 2020)
This research aims to assess the job satisfaction of workers of various IT employees in the Health care sector. It focuses on the relative relevance of factors of job satisfaction and their impact on employee’s actual job satisfaction. A sample of 114 employees from the hospital sector was used for this analysis. The study indicates the organizational development, policies of compensation and benefit, promotion and career development, work task, relationship with supervisor of the hospital are major factors of job satisfaction. The study is useful for evaluating employee satisfaction with their careers, whether or not they like jobs or specific aspects or measurements of work, such as job efficiency and supervision.